2017
DOI: 10.1186/s13756-017-0233-9
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use and antimicrobial susceptibility in Escherichia coli on small- and medium-scale pig farms in north-eastern Thailand

Abstract: BackgroundIntensification of livestock production seen in many low- and middle-income countries is often believed to be associated with increased use of antimicrobials, and may hence contribute to the emergence of antimicrobial resistance. The aim of this study was to map antimicrobial use on small- (n = 25) and medium-scale (n = 27) pig farms in north-eastern Thailand, and to compare antimicrobial susceptibility of commensal Escherichia coli isolated from sows on these farms.MethodsInformation regarding pig h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
26
3
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 23 publications
16
26
3
4
Order By: Relevance
“…As supermarkets generally source their meat from industrial farms, this suggests higher levels of AMU in smaller farms [ 123 ]. However, another study on Thai pig farms reported the higher levels of antimicrobial usage in medium farms compared with small farms [ 99 ]. Although income limitations among farmers in LMICs may theoretically result in lower levels of AMU, in practice this may be offset by a higher incidence of infectious diseases, easier access to veterinary drugs, limited veterinary services, and generally looser legislative enforcement [ 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…As supermarkets generally source their meat from industrial farms, this suggests higher levels of AMU in smaller farms [ 123 ]. However, another study on Thai pig farms reported the higher levels of antimicrobial usage in medium farms compared with small farms [ 99 ]. Although income limitations among farmers in LMICs may theoretically result in lower levels of AMU, in practice this may be offset by a higher incidence of infectious diseases, easier access to veterinary drugs, limited veterinary services, and generally looser legislative enforcement [ 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this problem of residual confounding cannot be eliminated completely in the context of routine data evaluation. In field studies, only a low number of pigs are sampled on one farm and only a small number of bacterial colonies are tested, which might not been representative of the species population on the respective farm [33].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in South-East Asia, antimicrobials are freely available over the counter for use in both humans and animals, therefore likely contributing to the extensive use in the livestock sector and the widely occurring AMR [ 7 , 8 , 9 ]. For instance, in Thailand, an extensive use of antimicrobials in the livestock sector has been documented, including agents considered to be critical for human medicine, such as aminoglycosides, fluoroquinolones and macrolides [ 2 , 10 , 11 ]. As a result, high levels of AMR in zoonotic bacteria, such as Salmonella and Campylobacter spp., have been reported along the animal-food production system [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%